Pembentukan dan Manifestasi Budaya Organisasi dalam Kajian Filsafat Islam - Mukaffan Mukaffan (Qolamuna : Jurnal Studi Islam, 2020)
This study aims to process the formation of organizational culture. The analysis results concluded, generally through four stages; (1) adaptation, which is the process of adjustment between leaders, members of the organization, the organization's external environment; (2) reconstruction, which is an effort to make significant changes by members of the organization. (3) implementation namely attempts to realize changes by previous planning without being separated from the organization's vision, mission, and strategy; and (4) the formation of organizational culture, namely the emergence of culture as a result of the idea, mission and strategy as well as the experience possessed by members of the organization in implementing change efforts in the organization. Keywords: Formation, Manifestation, Organizational Culture, Islamic Philosophy.